1 Answer | Add Yours
You need to start from the given derivative of the function and go to the original function. The operation you need to use is integration.
`int ((1-lnx)dx)/x^3 = int dx/x^3 - int (ln x dx)/x^3`
You need to solve the integrals separately such that:
`int dx/x^3 = int x^(-3)dx = (x^(-3+1))/(-3+1) + c`
`int dx/x^3 = -1/(2x^2) + c`
You need to use integration by parts to solve int (ln x dx)/x^3.
`u =ln x=gt du = dx/x`
`` `dv = dx/x^3 =gt v =-1/(2x^2)`
Use the formula of integration by parts:
`int udv = uv - int vdu`
`` `int (ln x dx)/x^3 = -ln x/(2x^2) + int dx/(2x^3)`
`int (ln x dx)/x^3 = -ln x/(2x^2) + (1/2)*(-1/(2x^2)) + c`
`int (ln x dx)/x^3 = (-1/(2x^2))*(ln x + 1/2) + c`
Evaluating the antiderivative of the given function yields:`int (ln x dx)/x^3 = (-1/(2x^2))*(ln x + 1/2) + c.`
We’ve answered 288,465 questions. We can answer yours, too.Ask a question